HS-23, a standardized extract of the dried flower buds of Lonicera japonica, has no major impact on drug transporters and on the pharmacokinetics of ceftriaxone and levofloxacin in rats - Kim, Ju Hyun; Kwon, Mihwa; Kwon, Soon Sang; Kim, Young-Mok; Hong, Sung-Woon; Yeon, Sung Hum; Song, Im-Sook; Lee, Hye Suk (Journal of pharmaceutical investigation, 2016)
Concurrent administration of herbal drugs that modulate drug transporter activities can cause herb–drug interactions in the process of the absorption, distribution, and elimination of drugs and thereby, modulate drug efficacy and toxicity. For this reason, regulatory agencies have instituted guidelines for the investigation of potential herb–drug interactions during the drug development process. Therefore, the purpose of this study was to investigate the herb–drug interaction potential of HS-23, an extract of the dried flower buds of Lonicera japonica , which is being evaluated for use in the treatment of sepsis in a phase II clinical study. The inhibitory effects of HS-23 on the transport functions of organic cation transporter (OCT)1, OCT2, organic anion transporter (OAT)1, OAT3, organic anion transporting polypeptide (OATP)1B1, OATP1B3, P-glycoprotein (P-gp), and breast cancer resistance protein (BCRP) were investigated in HEK293 and LLC-PK1 cells. The effects of HS-23 on the pharmacokinetics of ceftriaxone and levofloxacin, common combination drugs for sepsis treatment were also examined in rats. HS-23 (up to 100 μg/mL) did not inhibit the in vitro transport activities of OCT1/2, OAT1/3, OATP1B1/1B3, P-gp, and BCRP or the pharmacokinetics of ceftriaxone and levofloxacin in vivo after a single intravenous dose of 40 mg/kg. In conclusion, HS-23 may not have significant herb–drug interactions with the prevalently used ceftriaxone and levofloxacin, in rats even at its effective dose.